1996
DOI: 10.1055/s-2007-1012041
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of Atrial Tachyarrhythmias After Non-Cardiac Thoracic Surgery by Infusion of Magnesium Sulfate

Abstract: The possible role of magnesium sulfate (MgSO4) infusion in the prevention of atrial tachyarrhythmias after non-cardiac thoracic surgery was evaluated through a prospective study of two hundred patients who underwent non-cardiac thoracic surgery. The patients (who fulfilled the following requirements among others: no myocardial infarction in the previous six months, normal renal function, no use of digitalis or antiarrhythmic drugs, not undergone emergency operations or video-assisted thoracic surgery), were ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
28
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(28 citation statements)
references
References 4 publications
0
28
0
Order By: Relevance
“…87 The use of the potential prophylactic properties of magnesium sulfate, digoxin, b-adrenergic receptor blockade, diltiazem, and amiodarone has been proposed. 107,108,[112][113][114][115] A meta-analysis supports the use of calcium-channel blockers and b-blockers in the general thoracic surgical population 111 ; however, following the publication of the POISE trial and a further meta-analysis, the use of b-blockade in patients undergoing low-risk or intermediate-risk noncardiac surgery is not supported. 116,117 Although there is no evidence that prophylactic digoxin is effective at reducing the incidence of supraventricular arrhythmias in esophagectomy patients, 112 a prophylactic infusion of amiodarone has been shown to significantly reduce the incidence of atrial fibrillation in patients undergoing transthoracic esophagectomy.…”
Section: Cardiovascular Issuesmentioning
confidence: 99%
“…87 The use of the potential prophylactic properties of magnesium sulfate, digoxin, b-adrenergic receptor blockade, diltiazem, and amiodarone has been proposed. 107,108,[112][113][114][115] A meta-analysis supports the use of calcium-channel blockers and b-blockers in the general thoracic surgical population 111 ; however, following the publication of the POISE trial and a further meta-analysis, the use of b-blockade in patients undergoing low-risk or intermediate-risk noncardiac surgery is not supported. 116,117 Although there is no evidence that prophylactic digoxin is effective at reducing the incidence of supraventricular arrhythmias in esophagectomy patients, 112 a prophylactic infusion of amiodarone has been shown to significantly reduce the incidence of atrial fibrillation in patients undergoing transthoracic esophagectomy.…”
Section: Cardiovascular Issuesmentioning
confidence: 99%
“…Magnesium sulphate is often used as an anti-arrhythmic agent in the perioperative setting as it reduces the rate of the sino-atrial node impulses and increases the refractory period of the atrioventricular node [63] Data on magnesium effectiveness are still conflicting. While Terzi et al [64] in a prospective, randomized, open, placebo controlled trial showed a statistically significant reduction in the incidence of SVA from 26.7% in the control group to 10.7% in the magnesium group, Saran et al [65] observed no reduction in the incidence of SVA with prophylactic magnesium, even though it reduced their incidence in the high risk cohort of patients undergoing pneumonectomy. Statin drugs, which have anti-inflammatory properties, have also been shown to be associated with a reduction in the incidence of post-pulmonary resection AF [66] but their use is not supported by clear evidence.…”
Section: Postoperative Arrhythmiasmentioning
confidence: 97%
“…Partial sympathectomy with epidural analgesia did not reduce atrial fibrillation after cardiac surgery and only marginally attenuated the incidence after thoracic surgery in a small study in which the control and treated arms were poorly matched for age [32,33]. Unless hypomagnesemia is present, the role of prophylactic administration of magnesium during general thoracic surgery to reduce the incidence of postoperative supraventricular arrhythmias is not clear and data are available only from one study in which some control patients who had hypomagnesemia received magnesium after randomization [34]. Intriguingly, the use of statins before thoracic or cardiac surgery has been associated with a reduced incidence of postoperative atrial fibrillation but further study is needed to determine whether this strategy can be added to proven prevention strategies [22 ,35 ].…”
Section: Preventionmentioning
confidence: 99%